PEMBELAJARAN BAHASA INGGRIS UNTUK ANAK-ANAK - Besral Besral (Ta'dib, 2010)
A large numbers of credits taken by college students in Undergraduate Program proved to be insufficient for their successful competition in the job market.  To deal with this issue, Teacher Training Colleges and Institution provided their graduates with several professional skills related to computer and internet, foreign language learning, and other vocational skills.  Some of the results of these programs are fruitful for the graduations; however, several ongoing activities need to be monitored and reviewed.  Although 'Hunting Tourists' has been the trade mark of the English Tadris Department, 'Teaching Engish for the Children' which will be implemented in the few years to come, may override the previous ones because of its advantages and practical values.Kata kunci:   Praktikum, pembelajaran, pendekatan, metode, strategi, teknik, bahasa Inggris, program.